Demographic Profile, Injury Patterns, and Manner of Deaths in Railway Track Fatalities: A Forensic Study - B. Vasanth Naik; K. Venkat Nagaraju (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: Railway track fatalities are a signi𿿿cant cause of medicolegal autopsies in India, with the increasing frequency of such incidents raising concerns about safety and trauma patterns. This study aimed to evaluate the demographic pro𿿿le, injury patterns, and manner of death among railway track fatalities inSecunderabad, Telangana. Methods: A retrospective observational study was conducted at the Department of Forensic Medicine and Toxicology, Gandhi Medical College, Secunderabad. A total of 100 railway track fatalities, subjected to medicolegal autopsies from 1st October 2023 to 30th September 2024, were included. Data were extracted from autopsy records, including demographic details, external and internal injuries, and the manner of death (suicide, accident, or homicide). Statistical analysis involved descriptive statistics and the chi-square test to assess associations between variables. Results: The majority of victims were males (82%), with the highest number of fatalities in the 41-50 years age group (22%). The manner of death was classi𿿿edas suicide (56%) and accident (44%), with no homicides reported. External injuries were most commonly abrasions and contusions (100%), followed by lacerations and amputations. Internal injuries were severe, with the brain being the most commonly affected organ (74%). The cause of death was primarily multiple injuries (74%). Conclusions: The study highlights the predominance of suicides among males in railway track fatalities. It emphasizes the need for targeted safety measures, particularly addressing the high incidence of suicides and accidental deaths. Further research is required to explore regional variations and to develop preventive strategies.